Iron-processing genotypes, nutrient intakes, and cadmium levels in the Normative Aging Study: Evidence of sensitive subpopulations in cadmium risk assessment. (October 2018) - Ciesielski, Timothy H.; Schwartz, Joel; Bellinger, David C.; Hauser, Russ; Amarasiriwardena, Chitra; Sparrow, David; Wright, Robert O.
Abstract: Background: Because iron and cadmium share common transport mechanisms, iron-processing protein variants such as HFE C282Y, HFE H63D, and Transferrin P570S may influence cadmium metabolism. Our aim was to evaluate associations between common HFE and Transferrin polymorphisms and toenail cadmium levels among older men. Methods: In a longitudinal cohort of men age 51–97, the Normative Aging Study (NAS), we evaluated toenail cadmium concentrations and missense single nucleotide polymorphisms (SNPs) in the HFE and Transferrin genes. We fit age-adjusted models to estimate associations between genotypes and toenail cadmium concentrations. We then considered potential interactions with smoking status, hemoglobin, and nutritional intakes known to modulate cadmium absorption. For the significant interactions, we also evaluated genotype specific effect estimates. Results: HFE and Transferrin genotypes were not associated with toenail cadmium concentrations in the main effect analyses, but there were significant interactions between HFE H63D and hemoglobin (pinteraction = 0.021), as well as HFE H63D and vitamin C intake (pinteraction = 0.048). Genotype specific effect estimates suggested: 1) an inverse relationship between hemoglobin and cadmium levels among HFE H63D homozygotes, and 2) an inverse relationship between vitamin C intake and cadmium levels that strengthens with the number of HFE H63D variant alleles a subject carries. Conclusions: These findings suggest that sensitive subpopulations defined by diet, hemoglobin level, and genotype may absorb more cadmium from their environment and thus should be considered in cadmium risk analyses. These findings are particularly relevant given the high prevalence of the H63D variant worldwide. Highlights: Interactions with HFE H63D suggest the existence of sensitive subpopulations. Among HFE H63D homozygotes: those with lower hemoglobin had higher toenail Cd. The link between low Vitamin C intake and high Cd is amplified with HFE H63D variants. Those with HFE H63D variants and low hemoglobin or Vitamin C may absorb more Cd.